Pengaruh Tingkat Upah, Pertumbuhan Ekonomi, dan Indeks Pembangunan Manusia (IPM) terhadap Ketimpangan Pendapatan pada Kabupaten/Kota di Provinsi Jambi - Merlyn Crushselia Naibaho; Siti Hodijah; Yohanes Vyn Amzar (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
The purpose of this study was to determine and analyze the effect of wage levels, economic growth, and the Human Development Index (HDI) on income inequality through labor absorption in the Districts/Cities of Jambi Province from 2020-2024. The research method used is a quantitative descriptive analysis using panel data regression with the Fixed Effect Model approach.  The analysis method used Eviews 12. The results showed of that partially, income inequality in the Districts/Cities of Jambi Province is significant positive influenced by the wage level variable, while economic growth does not have a significant effect on income inequality. In addition, the Human Development Index (HDI) has a significant negative effect on income inequality. This implies that wage increases are actually followed by in income inequality. Meanwhile, economic growth has not been able to provide a broad income redistribution effect. Conversely, improving the quality of human development proves to be the most effective factor, as it is capable of significant reducing inequalirt levels. Simultaneously, the results show that the variables of wage levels, economic growth, and the Human Development Index (HDI) collectively have a significant influence on income inequality in Districts/Cities of Jambi Province.